Tindak Tutur Ilokusi dalam Cerpen Robohnya Surau Kami Karya A.A. Navis - Santi Maulinawati; Wardedy Rosi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research examines illocutionary speech acts according to Searle's theory in the short story Robohnya Surau Kami by A.A. Navis. This research aims to describe the form of illocutionary speech acts in the short story Robohnya Surau Kami by A.A. Navis, describes the contextual meaning in the short story Robohnya Surau. This research uses qualitative research with a stylistic approach. The research data used are dialogues in the form of words, phrases, clauses, and even discourse that indicates illocutionary speech acts. The source of research data is the short story Robohnya Surau Kami by A.A. Navis. The results of this research found utterances that were indicated as illocutionary speech acts in the short story Robohnya Surau Kami by A.A. Navois as many as 15 stories. Based on 15 speech data, four types of illocutionary speech acts and their forms were found, namely assertive speech acts totaling 8 utterances (stating 5 utterances, suggesting 3 utterances, and complaining 1 utterance), directive speech acts totaling 2 utterances (ordering 1 utterance and giving orders 1 utterance), expressive speech act of 1 utterance (blame 1 utterance), and declarative speech act of 3 utterances (surrender 1 utterance, decides on 1 utterance, and permits 1 utterance). The meaning of the speech is adjusted to the context of the speech. From these results, the form of assertive speech acts is most often found in the short story Robohnya Surau Kami by A.A. Navis.